Development of a potentiometric kinetic method for drug adsorption studies: The chlorpromazine-charcoal model case - AttaPolitou, J; Koupparis, M.; Macheras, P. (EUROPEAN JOURNAL OF PHARMACEUTICAL SCIENCES, 1996)
A potentiometric method for the in vitro adsorption kinetic study of an ionic micromolecule to charcoal, based on the continuous direct monitoring of the micromolecule free concentration by means of an ion-selective electrode (ISE), has been developed. A chlorpromazine ISE was constructed and used to study the adsorption kinetics of the drug on pure activated charcoal and two commercial formulations (Ultracarbon tablets and Carbomix powder). The method consists of the rapid addition of a slurry containing the charcoal into the drug solution under stirring at pH 1.2 (to simulate a gastric fluid environment) and continuous recording of the electrode potential until the establishment of equilibrium The drug free concentration at appropriate time intervals was calculated from the recorded adsorption curve acid the apparent adsorption rate constant was estimated assuming first order kinetics. Within run RSD of the estimates ranged from 0.3 to 12% (mainly less than 5%), while between run RSD (n=3) ranged from 1 to 19% (mainly less than 10%). A linear relationship was found between the apparent adsorption rate constants and the amount of charcoal used with slopes following the rank order activated charcoal>Ultracarbon tablets>Carbomix powder. These results were explained on the basis of different surface areas of the adsorbents. The work proved the usefulness of ion-selective potentiometry in adsorption studies and can be extended to other ionic drugs for which selective electrodes can be constructed.
Keywords: adsorption kinetic study; charcoal adsorption; chlorpromazine; ion-selective potentiometry